Thematic Teaching Media Development for Counseling Guidance in Primary Schools: A Need Analysis - Adi Prehanto; Asep Nuryadin; Nizza Nadya Rachmani; Iftia Nur Azizah (Jurnal Pendidikan Humaniora, 2022)
This research aimed to acquire comprehensive insights into the requirement for the development of teaching media in Elementary School Counseling Guidance. Utilizing a descriptive quantitative methodology, the study incorporated an investigative approach via literature reviews and expert consultations. The participants encompassed elementary school counseling guidance teachers. The data analysis process entailed data presentation and subsequent interpretation for generalizations. The findings revealed a distinct need for the development of instructional materials in schools, which teachers can implement through strategies or techniques tailored to developing interactive media, aligning with student characteristics. The study implies that instructional materials constitute a vital component of learning resources to enhance the student learning environment, particularly through the cultivation of interactive teaching materials.